PERNIKAHAN USIA MUDA DI DESA BAGIK PAYUNG SELATAN, LOMBOK TIMUR - Anas Mujahiddin (Prodi. Hukum Ekonomi Syariah, Fakultas Syariah, IAI Hamzanwadi Pancor Lombok Timur, 2023)
This article examines young marriages in Bagik Payung Selatan Village, Suralaga District, East Lombok. There are two main problems studied, namely the causes of the rise of easy marriages in the region and the factors that cause them. In collecting data, the writer used interview, observation and documentation techniques as primary data and took important data from books, journals and other scientific works related to the main theme of this research. After going through these series of steps, the authors found (1) The implementation of young marriages in Bagik Payung Selatan Village occurred because neither counseling nor socialization had been carried out regarding the issue of young marriage and customs from the past until now are still valid in society. (2) In detail, the occurrence of young marriages is caused by several factors including the low education of the bride and groom, low parental education, parents' economic situation, environmental factors or promiscuity and lack of youth activities. The impact caused by marriage at a young age is the frequent occurrence of disputes between husband and wife which include disharmony in the family, marriage at a young age not only has an impact on the health of the husband and wife but also has an impact on infant mortality and family resilience.